Parent Education Program: A space for reflection and guidance. (Journal of Parents and Teachers, 2025)
The article presents the idea of creating a Parent Education Program aimed at providing a space for reflection and guidance for all parents who have concerns about how their children learn or who want to learn strategies to help them. Additionally, the article is divided into sections to organize the information according to the questions to be answered.
Keywords: Parent Education Program; guidance; children; help